I-MASnBr3 /CZTGS Heterojunction Solar Cell Layer Optimization Investigated Using Scaps-1D Software Exhibited Excellent Performance at 50 % - Ghaleb M.; Arrar A.; Hadji Chikh A.; Bendjilali H.; Zerrouki O. (Annals of West University of Timisoara: Physics)
This paper reports a novel prototype of heterojunction solar cells based on semiconductor/perovskite structure using the solar cell capacitance one-dimensional simulator (SCAPS 1D). The device schematic consists of Glass/ITO/ETL/MASnBr3 /CZTGS/HTL layers with perovskite i-MASnBr3 as the permeable layer. The thickness of the absorber layer, carrier charge concentration, and the effect of temperature and series resistances are optimized. The research examines several critical parameters essential for solar cell performance, including a power conversion efficiency PCE of 50%, an open-circuit voltage Voc of 1.62 V, a fill factor FF of 91.5%, and a short-circuit current density Jsc of -34.06 mA/ cm2. The temperature and series resistance effects, as well as quantum efficiency QE, and J-V curve simulations with varying acceptor density, are investigated.